Madrasah sebagai Inkubator Komunitas dalam Peningkatan Kualitas Sosial-Ekonomi Masyarakat Pulau Lancang Besar - Nimpuno, Wibisono Bagus; Hasbi, Rahil M.; Jamila, Rona Fika; Vidiyanti, Christy; Putra, Gentina Pratama (CV. IRA PUBLISHING, 2024)
This community service program was conducted at Madrasah Diniyah Thoyyibah Islamiyah, Pulau Lancang Besar, with the aim of encouraging community participation in improving the physical quality of the madrasah environment and establishing the madrasah as an incubator for local socio-economic development. This initiative represents the university's contribution to the Community Action Plan (CAP) program initiated by the Jakarta Provincial Government in 2021 on Pulau Lancang Besar. The previously implemented CAP program primarily focused on the physical aspects of environmental improvement for restructuring slum settlements, leaving socio-economic issues as a lower priority. Through this community service program, socio-economic aspects were integrated into environmental improvement efforts, with the madrasah serving as the primary driver. Participatory discussions were held with the community to design and implement programs aimed at enhancing the physical, social, and economic quality of the community, with the university acting as a partner in planning and implementation support. The program outcomes demonstrated improvements in the madrasah's physical environment, strengthened its role as a center for social and economic activities, and increased active community involvement, fostering a stronger sense of ownership and shared responsibility. The integration of physical improvements and socio-economic development has proven to contribute significantly to community development, particularly in areas with limited government support. This self-managed madrasah successfully served as an effective incubator model for social and economic transformation, although the economic impacts are not yet significantly evident.